Complement-Opsonized HIV-1 Alters Cross Talk Between Dendritic Cells and Natural Killer (NK) Cells to Inhibit NK Killing and to Upregulate PD-1, CXCR3, and CCR4 on T Cells - Ellegård, Rada; Khalid, Mohammad; Svanberg, Cecilia; Holgersson, Hanna; Thorén, Ylva; Wittgren, Mirja Karolina; Hinkula, Jorma; Nyström, Sofia; Shankar, Esaki M.; Larsson, Marie (Frontiers in Immunology, 2018)
Dendritic cells (DCs), natural killer (NK) cells and T cells play critical roles during primary HIV-1 exposure at the mucosa, where the viral particles become coated with complement fragments and mucosa associated antibodies. The microenvironment together with subsequent interactions between these cells and HIV at the mucosal site of infection will determine the quality of immune response that ensues adaptive activation. Here, we investigated how complement and immunoglobulin opsonization influences the responses triggered in DCs and NK cells, how this affects their crosstalk, and what T cell phenotypes are induced to expand following the interaction. Our results showed that DCs exposed to complement-opsonized HIV were less mature and had a poor ability to trigger IFN-driven NK cell activation. In addition, when the DCs were exposed to complement opsonized HIV, the cytotolytic potentials of both NK cells and CD8 T cells were markedly suppressed. The expression of PD-1, as well as co-expression of negative immune checkpoints TIM-3 and LAG-3 on PD-1 positive cells were increased on both CD4 as well as CD8 T cells upon interaction with and priming by NK-DC cell crosstalk cultures exposed to complement opsonized HIV. In addition, stimulation by NK-DC crosstalk cultures exposed to complement opsonized HIV led to the upregulation of CD38, CXCR3, and CCR4 on T cells. Together, the immune modulation induced during the presence of complement on viral surfaces is likely to favor HIV establishment, dissemination, and viral pathogenesis.